Spice model for TIO2 memristive switching / Nur Liyana Anuar - Anuar, Nur Liyana (2014)
This research project with due to some of practical issues affecting SPICE model, it focuses on the determination of switching mechanisms that were affects a SPICE model for the titanium dioxide memristor device. To have memristors as a feature in IC Design technology, the model for simulation needs to be fully understood for switching. Other than that, fabrication link with model needs to be fully established. The research project objectives to establish a link between model parameter based on actual measured data from in house fabrication samples. The taken data is used to establish the device parameter and implement to a simple memristor circuit in order to analyze circuit performance. In order to develop a spice model parameter for a memristor, there are two ways been used in this research project which collecting and analyze the data of sample comparison. The device simulation tested by using a simple digital circuit and compared with an existing spice model. Consequently, a clear link is established between actual fabrication and circuit performance. The device behavior can be linked in between the fabrication and circuit performance. This behavior is affecting the relationship for IV characteristic and the switching value.